2023
DOI: 10.1002/jcsm.13364
|View full text |Cite
|
Sign up to set email alerts
|

The role of extracellular vesicles in skeletal muscle wasting

Xiaohui Zhang,
Yanxia Zhao,
Wei Yan

Abstract: Skeletal muscle wasting is a complicated metabolic syndrome accompanied by multiple diseases ranging from cancer to metabolic disorders and infectious conditions. The loss of muscle mass significantly impairs muscle function, resulting in poor quality of life and high mortality of associated diseases. The fundamental cellular and molecular mechanisms inducing muscle wasting have been well established, and those related pathways can be activated by a variety of extracellular signals, including inflammatory cyto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 87 publications
(211 reference statements)
0
4
0
Order By: Relevance
“…Study from the same research group further demonstrated that growth differentiation factor 15 (GDF-15) presented in CRC cells-derived exosomes could also directly induce apoptosis of myocytes via regulating Bcl-2/caspase-3 pathways [ 184 ]. Collectively, these studies suggested that cargoes in cancer cells-derived exosomes play important roles in development of cachexia and may act as valuable therapeutic targets in exploring novel treatment in the future [ 185 , 186 ].…”
Section: Tumor Biology Of Exosomesmentioning
confidence: 99%
“…Study from the same research group further demonstrated that growth differentiation factor 15 (GDF-15) presented in CRC cells-derived exosomes could also directly induce apoptosis of myocytes via regulating Bcl-2/caspase-3 pathways [ 184 ]. Collectively, these studies suggested that cargoes in cancer cells-derived exosomes play important roles in development of cachexia and may act as valuable therapeutic targets in exploring novel treatment in the future [ 185 , 186 ].…”
Section: Tumor Biology Of Exosomesmentioning
confidence: 99%
“…Muscle wasting and atrophy are significant characteristics of CC [ 63 , 64 ]. Recent evidence indicates that EVs play a crucial role in the muscle wasting associated with CC [ 65 ]. Research has demonstrated that EVs originating from cancer cells directly influence skeletal muscle cells, leading to muscle wasting (Fig.…”
Section: Evs and Pathogenesis Of CCmentioning
confidence: 99%
“…Cancer cell-derived exosomes may play important roles in the communication between cancer tissue and skeletal muscle (or adipose tissue). The nucleic acids, lipids, or proteins in these exosomes may contribute to the biological processes underlying cancer-related cachexia, including regulating lipidolysis and skeletal muscle atrophy [ 27 29 ]. Meanwhile, stem cell-derived exosomes have demonstrated therapeutic effects in improving skeletal muscle regeneration [ 30 , 31 ].…”
Section: Introductionmentioning
confidence: 99%